Given:
• P(x) = x² - 4x +3
To find :
• The zeroes of the quadratic polynomial .
• To verify the relationship .
Solution :
•x² - 4x + 3 = 0
Split the middle term :
=> x² - 3x - x + 3 = 0
=> x ( x - 3) - 1 ( x - 3 ) = 0
=> (x - 1)( x - 3 ) = 0
• x - 1 = 0
=> x = 1 .
• x - 3 = 0
=> x = 3 .
Hence , the zeroes are 1 and 3 .
Now , verification :
• x² - 4x +3 .
compare with ax² + bx + c we get ,
• a = 1 , b = -4 and c = 3 .
As we know that :
• Sum of Zeroes = -b/a
=> 1 + 3 = -(-4)/1
=> 4 = 4
LHS = RHS .
NOW ,
• Product of Zeroes = c/a
=> 1(3)= 3/1
=> 3 = 3
LHS = RHS .
Hence, Verified .
I hope it will help you.
Regards